Tribbles-2 is a novel regulator of inflammatory activation of monocytes - Eder, Katalin (Oxford University Press, 2008)
Inflammatory activation of monocytes is an essential part of both innate immune responses and the pathogenesis of conditions such as atherosclerosis. However, the mechanisms which modulate the response of monocytes to inflammatory stimuli are still poorly understood. Here, we report that tribbles-2 (trb-2) is a novel regulator of inflammatory activation of monocytes. Down-regulation of trb-2 levels potentiates LPS-induced IL-8 production via enhanced activation of the extracellular signal-regulated kinase and jun kinase mitogen-activated protein kinase (MAPK) pathways. In keeping with this, the endogenous level of trb-2 expression in human primary monocytes is inversely correlated to the cell’s ability to produce IL-8. We show that trb-2 is a binding partner and a negative regulator of selected MAPKs. The potential in vivo relevance of these findings is highlighted by the observation that modified low-density lipoprotein profoundly down-regulates trb-2 expression, which may, in turn, significantly contribute to the inflammatory processes in the development of vascular disease. Taken together, our results define trb-2 as a potent novel regulator of monocyte biology, controlling the activation of these cells.